Hydrothermal Alteration of Ultramafic Rocks in Ladon Basin, Mars—Insights From CaSSIS, HiRISE, CRISM, and CTX. Issue 1 (5th January 2023) - Mège, Daniel; Gurgurewicz, Joanna; Massironi, Matteo; Pozzobon, Riccardo; Tognon, Gloria; Pajola, Maurizio; Tornabene, Livio L.; Lucchetti, Alice; Baschetti, Beatrice; Davis, Joel M.; Hauber, Ernst; De Toffoli, Barbara; et al.
Abstract: The evolution of the Ladon basin has been marked by intense geological activity and the discharge of huge volumes of water from the Martian highlands to the lowlands in the late Noachian and Hesperian. We explore the potential of the ExoMars Trace Gas Orbiter/Color and Stereo Surface Imaging System color image data set for geological interpretation and show that it is particularly effective for geologic mapping in combination with other data sets such as HiRISE, Context, and Compact Reconnaissance Imaging Spectrometer for Mars. The study area displays dark lobate flows of upper Hesperian to early Amazonian age, which were likely extruded from a regional extensional fault network. Spectral analysis suggests that these flows and the underlying rocks are ultramafic. Two distinct altered levels are observed below the lobate flows. The upper, yellow‐orange level shows hundreds of structurally controlled narrow ridges reminiscent of ridges of listwanite, a suite of silicified, fracture‐controlled silica‐carbonate rocks derived from an ultramafic source and from serpentine. In addition to serpentinite, the detected mineral assemblages may include chlorite, carbonates, and talc. Kaolin minerals are detected in the lower, white level, which could have formed by groundwater alteration of plagioclase in the volcanic pile. Volcanism, tectonics, hydrothermal activity, and kaolinization are interpreted to be coeval, with hydrothermal activity and kaolinization controlled by the interactions between the aquifer and the hot, ultramafic lobate flows. Following our interpretations, East Ladon may host the first listwanite ridges described on Mars, involving a hydrothermal system rooted in a Hesperian aquifer and affecting ultramafic rocks from a magmatic source yet to be identified. Plain Language Summary: The payload of the ExoMars Trace Gas Orbiter spacecraft includes the Color and Stereo Surface Imaging System (CaSSIS) camera, which retrieved its first Mars images in 2018. Its strength lies in the combination of spatial and spectral resolution with stereo capabilities made possible by a rotating platform. This study investigates the complementarity between the color images of CaSSIS and other data sets from the Mars Reconnaissance Orbiter: the HiRISE camera, the Context camera, and the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) hyperspectral imager. In this study, we show how CaSSIS readily reveals composition variations at the surface, such as dark flows and light‐toned zones in the underlying rocks. Using CRISM and CaSSIS data, their composition can be determined. It is found that the flows are probably volcanic and that the lighter‐toned rocks are hydrothermally altered versions of these rocks. This alteration takes the form of listwanite, mineral assemblage found on Earth in mantle rocks transported to the continental surface after subduction, such as the Oman ophiolites. Our findings make the late geologic history of the eastern Ladon basin singularly complex, a unique groundwater‐controlled environment conducive to the formation of base and rare metal deposits. Key Points: We evaluate the contribution of Color and Stereo Surface Imaging System (CaSSIS) color images in the Ladon basin where high‐resolution data sets (HiRISE, Context, and Compact Reconnaissance Imaging Spectrometer for Mars [CRISM]) are available Data analysis suggests Amazonian ultramafic volcanism and listwanitization in East Ladon CaSSIS color images fill the gap between color HiRISE images and CRISM hyperspectral data